Development of Kotta Cinna Site Museum in Medan City, 2008-2023 - Jelita Tua Nainggolan; Abdul Karim Batubara (Warisan: Journal of History and Cultural Heritage, 2024)
his study explores the development of the Kotta Cinna Site Museum in Medan City from 2008 to 2023. The background of this research underscores the importance of cultural heritage preservation amidst rapid urbanization and the role of museums as cultural institutions in education and conservation. The primary research question posed is how the Kotta Cinna Site Museum has evolved over this period and its impact on the local community. The research methodology includes literature review, in-depth interviews with stakeholders, and field observations. The findings indicate significant advancements in the museum's facilities, collections, and educational programs, contributing to heightened public awareness of cultural heritage importance. The author concludes that despite challenges in funding and management, the Kotta Cinna Site Museum has positively impacted cultural preservation and community education.